2013
DOI: 10.4103/0253-7613.106443
|View full text |Cite
|
Sign up to set email alerts
|

Sodium valproate induced increased frequency of micturition and enuresis

Abstract: Sodium valproate is a commonly used antiepileptic drug (AED) for control of a broad range of seizures. Adverse drug reactions (ADR) due to sodium valproate range from sedation to nausea, vomiting, weight gain, idiosyncratic adverse effects like hepatotoxicity and life threatening conditions like pancreatitis. We present a case of sodium valproate induced enuresis in child. This ADR of valproate is an underreported ADR and requires special attention of pediatricians as it can interfere with the further treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Furthermore, the mean daily dose of valproate was not significantly different among children who developed this adverse event and those who did not, a finding that suggests that the occurrence of secondary enuresis is not dose related. Data from individual case reports suggest that, at least in some children, nocturnal enuresis is dose related since it was noted only when valproate dose was increased …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the mean daily dose of valproate was not significantly different among children who developed this adverse event and those who did not, a finding that suggests that the occurrence of secondary enuresis is not dose related. Data from individual case reports suggest that, at least in some children, nocturnal enuresis is dose related since it was noted only when valproate dose was increased …”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies and case reports evaluating the adverse events associated with valproate mentioned enuresis as a possible side effect of this drug with a frequency, when reported, ranging between 2% and 7%. [7][8][9][10][11]14,15 In a retrospective study of 100 children, which evaluated the frequency and amount of weight gain after exposure to valproate, nocturnal enuresis was reported in 7% of participants; however, further details, other than the fact that enuresis spontaneously abated after a few months, were not provided. 7 In a prospective comparative trial of phenobarbital, primidone, and valproate for the prevention of febrile seizures, 1 child out of 48 children (2%) exposed to valproate was reported to have developed enuresis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the literature, these side effects are more likely to occur in patients who require dosage increase. Despite these reports, there is a lack of solid evidences on association of urinary complications with sodium valproate and thus these complications are not known as side effects of this drug (11,13,14). Egger and Brett performed a retrospective study on the side effects of sodium valproate on epileptic children focusing on weight gain, they showed that among 100 cases, only 7% exhibited enuresis as a side effect (15).…”
Section: Discussionmentioning
confidence: 99%
“…Our literature search identified 14 case reports that described the induction of enuresis in children with epilepsy who were treated with SV, but there was an absence of literature examining nonepileptic patients 49. Moreover, none of the patients presented with diurnal enuresis.…”
Section: Discussionmentioning
confidence: 99%